2021
DOI: 10.3748/wjg.v27.i46.7956
|View full text |Cite
|
Sign up to set email alerts
|

T cells in pancreatic cancer stroma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly devastating disease with a dismal 5-year survival rate. PDAC has a complex tumour microenvironment; characterised by a robust desmoplastic stroma, extensive infiltration of immunesuppressive cells such as immature myeloid cells, tumour-associated macrophages, neutrophils and regulatory T cells, and the presence of exhausted and senescent T cells. The cross-talk between cells in this fibrotic tumour establishes an immune-privileged microenvironment that suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 85 publications
(141 reference statements)
3
36
0
Order By: Relevance
“…Interestingly, and in in line with Büll et al, [ 12 ] we found that Ac 5 3F ax Neu5Ac had the potency to reduce SA expression in the established subcutaneous pancreatic tumors, with this decrease being significant in the reduction of α2,3-SA in the 10 mg/kg group; moreover, blocking SA expression altered the tumor microenvironment, leading to an increase of the immune cell to tumor cell ratio in the treated tumors. Although the infiltration of immune cells was low, which is in accordance with the fact that PDA tumors are described to have low immune component [ 32 ], we detected a marked increase in tumor infiltrating CD4 + and CD8 + T cells and NK cells, which are indicators of a reversion of the immunosuppressive tumor microenvironment [ 33 , 34 ]. Although it was not statistically significant, we also observed increasing percentages of granulocytes and monocytes, cells that are usually classified as immunosuppressive ones.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, and in in line with Büll et al, [ 12 ] we found that Ac 5 3F ax Neu5Ac had the potency to reduce SA expression in the established subcutaneous pancreatic tumors, with this decrease being significant in the reduction of α2,3-SA in the 10 mg/kg group; moreover, blocking SA expression altered the tumor microenvironment, leading to an increase of the immune cell to tumor cell ratio in the treated tumors. Although the infiltration of immune cells was low, which is in accordance with the fact that PDA tumors are described to have low immune component [ 32 ], we detected a marked increase in tumor infiltrating CD4 + and CD8 + T cells and NK cells, which are indicators of a reversion of the immunosuppressive tumor microenvironment [ 33 , 34 ]. Although it was not statistically significant, we also observed increasing percentages of granulocytes and monocytes, cells that are usually classified as immunosuppressive ones.…”
Section: Discussionsupporting
confidence: 84%
“…PDAC stroma can also be infiltrated by T and myeloid cell populations [ 13 , 14 ], and patients with the higher proportions of CD8 + and CD4 + T cells together with dendritic cells have improved prognosis [ 15 ]. T cells are predominantly antigen-experienced effector memory T cells, with the potential to activate immune response [ 16 , 17 ]. However, the PDAC microenvironment contains also multiple immunosuppressive cells, such as regulatory T cells (Tregs) and myeloid-derived suppressor cells (MDSCs), that inhibit T cell activation and are associated with tumour-permissive anergy and poor prognosis [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Signature genes for clustering and annotation of each cluster were in accordance with well-known cell markers recorded in the literature. 7 , 9 , 31 , 32 , 33 , 34 , 35 Figure 1 B illustrates trackplot of qualitative gene expression profiles of different T cell phenotypes including the exhausted, senescent, and cytotoxic T cell subtypes. Figure 1 C shows the UMAP dimensionality reduction embedding of the ∼13,500 T cells from the combined PDAC transcriptome colored by orthogonally generated clusters labeled by manual cell type annotation.…”
Section: Resultsmentioning
confidence: 99%